Pakistan : Twelfth and Final Review Under the Extended Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Proposal for Post-Program Monitoring-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Pakistan's Twelfth and Final Review Under the Extended Arrangement, Request for Waivers of Nonobservance of Performance Criteria (PCs), and Proposal for Post-Program Monitoring. The authorities met most PCs at end-June 2016, but the PCs on the budget deficit and Net Domestic Assets (NDA) of the State Bank of Pakistan were missed by small margins. They also met all program indicative targets. Structural benchmarks on financial sector reform, privatization, and energy sector reform were met. The IMF staff supports the authorities' request for completion of the twelfth review under the arrangement and for waivers for nonobservance of the end-June PCs on the budget deficit and NDA.